The complete guide to the TOEFL Test : - Rogers, Bruce (Thomson Asia, 2007)
The instruction and practice in "The complete guide to the TOEFL Test : Speaking, iBT Edition, helps students master the skills necessary to achieve the best possible score on the reading section of the TOEFL iBT, and to prepare them for success in an academic setting. The book includes: Special note taking tutorial; test-taking strategies; step-by-step lessons; an interactive CD-ROM and the audio program on CD or tape.